Distracting the masses: Art, local government and freedom of political speech in Australia - K. Gelber (Law Text Culture, 2006)
Visual images in the form of politically explicit street art can evoke passionate responses. In the arena of political culture these responses can be educative or vilificatory, constructive or abusive, and form part of public debate. Where these images are censored, restricted or banned through legal intervention by government, however, the debate takes on a different tone because it interacts with free speech principles. What are the limitations of valid government intervention against controversial political art? Is it justifiable, and if so when and under what circumstances, for government to censor political views with which it disagrees or which it may consider hurtful or offensive to members of the community within which the art is exhibited? What are the limits to legal regulation of politically controversial works of visual culture?